Chlorhexidine oral rinses for symptomatic COPD: a randomised, blind, placebo-controlled preliminary study - Alexa A Pragman; Ann M Fieberg; Cavan S Reilly; Christine Wendt (BMJ Open)
Objectives Determine the effect of twice-daily chlorhexidine oral rinses on oral and lung microbiota biomass and respiratory symptoms.Setting Single centre.Participants Participants were aged 40–85 with chronic obstructive pulmonary disease (COPD) and chronic productive cough or COPD exacerbation within the last year. Exclusions included antibiotics in the previous 2 months and/or those with less than four teeth. Forty-four participants were recruited and 40 completed the study.Intervention Participants were randomised 1:1 to twice-daily 0.12% chlorhexidine oral rinses versus placebo for 2 months along with daily diaries. St. George’s Respiratory Questionnaire (SGRQ), blood tests, oral rinse and induced sputum were collected at randomisation and the final visit.Primary and secondary outcomes Primary outcome was a change in oral and sputum microbiota biomass. Secondary outcomes included: sputum and oral microbiota Shannon and Simpson diversity and taxonomy; inflammatory markers; Breathlessness, Cough and Sputum Scale and SGRQ scores.Results Neither the oral microbiota nor the sputum microbiota biomass decreased significantly in those using chlorhexidine compared with placebo (oral microbiota mean log10 difference (SE)=−0.103 (0.23), 95% CI −0.59 to 0.38, p=0.665; sputum microbiota 0.80 (0.46), 95% CI −0.15 to 1.75, p=0.096). Chlorhexidine decreased both oral and sputum microbiota alpha (Shannon) diversity (linear regression estimate (SE) oral: −0.349 (0.091), p=0.001; sputum −0.622 (0.169), p=0.001). Chlorhexidine use did not decrease systemic inflammatory markers compared with placebo (C reactive protein (chlorhexidine 1.8±7.5 vs placebo 0.4±6.8, p=0.467), fibrinogen (22.5±77.8 vs 10.0±77.0, p=0.406) or leucocytes (0.2±1.8 vs 0.5±1.8, p=0.560)). Chlorhexidine use decreased SGRQ scores compared with placebo (chlorhexidine −4.7±8.0 vs placebo 1.7±8.9, p=0.032).Conclusions We did not detect a significant difference in microbiota biomass due to chlorhexidine use. Chlorhexidine decreased oral and sputum microbiota alpha diversity and improved respiratory health-related quality of life compared with placebo.Trial registration NCT02252588.